Implementasi dan Pemanfaatan E-Marketing untuk Optimalisasi Business to Business di Bank Sampah Sekar Melati Kabupaten Kudus - Diana Laily Fithri; Andy Prasetyo Utomo; Fajar Nugraha (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Mlati Norowito Village, Kudus Regency has a waste bank, namely the Sekar Melati Waste Bank. The Sekar Melati Waste Bank plays an active role in processing waste, especially non-organic waste. Sekar Melati Waste Bank has produced processed non-organic waste in the form of bags and tissue holders. This product is marketed outside Java. The marketing carried out is still in the form of word of mouth and traditional marketing. The purpose of this community service is to help increase the income and welfare of Sekar Melati Waste Bank partners in Kudus Regency by utilizing information technology, especially in the field of marketing based on e-marketing and business to business. The methods used are: lectures, training, and mentoring. The results achieved are: 1) partners understand well the benefits of B2B, e-marketing, and e-commerce; 2) partners have social media accounts to conduct e-marketing so as to cut labor costs, advertising costs and so on;3) partners understand how to create an account and make sales on e-commerce or market places.